(untitled) (Indian Journal of Public Health Research & Development, 2026)
Background: Aging is associated with a decline in physical function, leading to reduced mobility and increased health risks. Physical activity is crucial for maintaining health and independence in older adults, yet its levels tend to decline with age, however, the gender differences in habitual physical activity among free-living older adults remain underexplored, particularly in the Indian context. The present study is undertaken to identify any significant gender-based differences in habitual level of physical activity in free-living older adults aged 65 to 85 years by using the Physical Activity Scale for Elderly (PASE) Methods: A cross-sectional study was conducted among 62 participants (31 men and 31 women) residing in Mysuru, recruited using convenience sampling. Data collection involved face-to-face interviews utilizing the PASE questionnaire, which assesses physical activity levels across occupational, household, and leisure domains over the past seven days. Statistical analysis was performed using an independent samples t-test to determine gender-based differences in habitual physical activity levels. Results: The study found a statistically significant gender difference in habitual physical activity levels. Men exhibited higher physical activity levels compared to women, as evidenced by a significant p-value (p < 0.001) and a large effect size (Cohen’s d = -1.25). Conclusion: This study highlights a clear gender difference in habitual physical activity levels among free-living older adults. Addressing these disparities through tailored interventions and policy initiatives can contribute to improved health outcomes and overall well-being in aging populations.